Pengaruh Penggunaan Fly Ash Sebagai Subtitusi Semen Terhadap Kapasitas Kuat Tekan Paving Block - Muh Ridha Abd Rahim; Mustakim Mustakim; Misbahuddin Misbahuddin (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
PLTU produces coal-burning residues in the form of fly ash waste, which is constantly increasing. Fly ash is an industrial waste that is hazardous to the environment and human health but can be exploited because it has the characteristics of pozzolan. We conducted research on the use of fly ash as a cement substitute in the making of paving blocks. The aim of the research was to find out the strong pressure paving block method in British Standard 6717 with SNI 03-0691-1996 against the use of fly ash and how much of the fly ash is used against the strength of the optimum pressure. The research used an experimental method, with a comparison of 1 cement with 4 sand and variations in the use of air ash at 0%, 10%, 20%, and 30%. Tests were conducted when paving the block through the process of curing for 28 days. This study resulted in a strong average pressure paving block (PB) using the British Standard fly ash method 6717, with PB beam variations of 10%, 20%, and 30% in succession of 14.23 MPa, 13.49 MPa, and 11.14 MPa. While the SNI method 03-0691 1996 is PB cube variation at 10%, 20%, and 30%, respectively, of 12.27 MPa, 10.63 MPa, and 8.67 MPa. The strong result of pushing PB beams using the optimum fly ash is found at a 10% variation of 14.23 MPa and a 10% cubic variation PB of 12.27 MPa.